Development of 220V Overcurrent Relay Protection System Based on Internet of Things - Hasibuan, Arnawan; Hafidzuddin, Muhammad; Misbahul Jannah; Jintaka, Dhandis Rito; Kerimzade G.S (Andalas Journal of Electrical and Electronic Engineering Technology, 2025)
Electrical protection is essential to keep electrical systems safe. A suitable protection system can create a safe situation in the event of an overcurrent or voltage drop in the power grid. This can be caused by various factors such as usage, short circuits, or other disturbances. An electrical load control system regulates and monitors power consumption to prevent overcurrents and short circuits. The current reading process uses the current sensor and voltage sensor PZEM-004T, and when the set consumption exceeds the consumption, the relay holds the electric load. Also, the LCD is used to display the power consumption, and the keypad is used to enter the power limit. On the other hand, remote monitoring uses NodeMCU ESP826. Arduino Uno R3 is also a microcontroller that controls the central system. This study aims to create a prototype to monitor, limit, adjust, and control energy consumption to minimize energy consumption. This tool can monitor current and voltage and limit electrical energy consumption if necessary. This research is expected to alleviate the problem of house fires caused by overcurrents.